The effectiveness of coercive measures in motivating vaccination: Evidence from China during the COVID-19 pandemic - Yue Guan (Global Public Health)
Governments worldwide have implemented mandates, restrictions, and other coercive measures to secure adequate vaccine coverage, with the COVID-19 pandemic providing numerous examples. While the ethics and public reception of such measures are matters of heated discussion, their effectiveness in motivating individuals to get vaccinated remains incompletely understood. This study addresses that gap by analyzing data from a 2022 nationwide online survey conducted in China. Respondents recruited through proportional quota sampling to reflect key demographic characteristics of the population were asked to specify their COVID-19 vaccination status and the reason behind their decision. Results reveal that while most respondents reported getting vaccinated voluntarily, 14.6% attributed their vaccination to the government’s coercive mobilisation efforts. Moreover, members of the ruling Chinese Communist Party, as well as individuals favouring Western vaccines unavailable in China, were more likely to cite coercive mobilisation as the reason for their vaccination. These findings suggest that coercive measures can motivate a substantial proportion of the population to get vaccinated, especially those closely connected to the political system and those with unmet vaccination preferences. Given the controversy surrounding such measures, this enhanced understanding of their effectiveness could help with formulating targeted policies to combat infectious diseases and safeguard public health.